People Management Practices Trends in Micro, Small and Medium Enterprises in the Philippines - Binghay, Virgel C. (Philippine Journal of Labor and Industrial Relations; Vol 32 No 1&2 (2012): Philippine Journal of Labor and Industrial Relations, 2021)
Micro, small and medium enterprises (MSMEs) have contributed to the economic and social advancement of many countries all over the world. This is especially true for developing nations like the Philippines, where MSMEs not only comprise almost all business establishments but also a bulk of its workforce. While institutional support has been set in place by government, challenges still remain for many MSMEs, particularly with regard to human resource management (HRM) in these establishments. Related literature reveal that HRM practices in these enterprises are often overlooked. This study primarily focuses on the poor people-management practices and policies, or the lack thereof, among MSMEs in the country. Stakeholders, particularly managers and workers, should pay heed to the poor HRM in these establishments, and improve on them in order to fully harness the potential that MSMEs offer.